Determinan Environmental, Social, and Governance (ESG) Reporting Perusahaan di Indonesia: Perspektif Teori Sustainability - Sri Astuti Lelani Putri; Mega Silvia (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study examines the relationship between green innovation, company size, and leverage on ESG Reporting in companies in Indonesia with a sample of 53 companies. Green Innovation is measured based on the number of green patents held by the company as a tangible indicator of commitment to sustainability, company size is measured using the natural logarithm of total assets, while leverage is measured based on the company's ability to pay off debts using its own capital. The results of the study indicate that green innovation has a positive effect on ESG Reporting, company size has no effect, and leverage has a negative effect. This finding is supported by sustainability theory, which emphasizes the importance of integrating environmental, social, and governance aspects into corporate strategies. Green innovation aligns with the principles of sustainability as it reflects a commitment to environmental preservation. The lack of influence from company size indicates that sustainability is more determined by the values and strategies of the company, rather than the scale of the business. Meanwhile, the negative influence of leverage suggests that financial pressure can hinder commitment to sustainability reporting. Overall, sustainability theory supports these findings.